2022
DOI: 10.1177/10711007221078000
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of the Progressive Collapsing Foot Deformity (PCFD) Classification

Abstract: Background: A consensus group recently proposed the term progressive collapsing foot deformity (PCFD) and a new classification with 2 stages plus 5 classes to describe the complex array of flatfoot deformities. This study aimed to validate different diagnostic accuracy rates of the PCFD classification. Methods: This was a survey-based study distributed among 13 foot and ankle fellowship programs for 3 groups of participants with varied experience in practice (group 1: fellows in training, group 2: surgeons in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Among the total, 35.4% reported that "increased hindfoot moment arm" in class A was difficult to use (19.5% considered the description unclear, 11% did not how to diagnose it, 5% considered the term inaccurate, and 5% considered this concept was not suitable for clinical use), 42.7% reported that "increased foot and ankle offset" in class A was difficult to use (14.6% considered the description unclear, 13.4% did not know the term, 8.5% did not know how to diagnosis it, and 6.1% considered this concept was not suitable for clinical use) (Figure 6), 13.4% reported that the term "Sinus tarsi impingement" in class B was difficult to use (4.9% considered "sinus tarsi impingement" had an unclear description with a missing reference range for diagnosis, interest with precision and accuracy (15,16) . Lee et al (7) tested the reliability, Li et al (8) evaluated the diagnostic accuracy, while our study investigated the content validity of the PCFD classification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the total, 35.4% reported that "increased hindfoot moment arm" in class A was difficult to use (19.5% considered the description unclear, 11% did not how to diagnose it, 5% considered the term inaccurate, and 5% considered this concept was not suitable for clinical use), 42.7% reported that "increased foot and ankle offset" in class A was difficult to use (14.6% considered the description unclear, 13.4% did not know the term, 8.5% did not know how to diagnosis it, and 6.1% considered this concept was not suitable for clinical use) (Figure 6), 13.4% reported that the term "Sinus tarsi impingement" in class B was difficult to use (4.9% considered "sinus tarsi impingement" had an unclear description with a missing reference range for diagnosis, interest with precision and accuracy (15,16) . Lee et al (7) tested the reliability, Li et al (8) evaluated the diagnostic accuracy, while our study investigated the content validity of the PCFD classification.…”
Section: Discussionmentioning
confidence: 99%
“…The PCFD classification has been found to have moderate interobserver reliability, very good intraobserver agreement (7) , and good diagnostic accuracy (8) . The aim of this study is to validate the content accuracy of the PCFD classification system, an important step when a newly introduced classification system is being widely adopted for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to establish the diagnostic reliability of a new classification for progressive collapsing foot deformity, Li et al 16 distributed a survey to current trainees, graduates, and faculty of 13 foot and ankle fellowship programs. For the entire cohort, the diagnostic accuracy rates were 71.0% overall, 78.3% for class, and 81.7% for stage.…”
Section: Pes Planusmentioning
confidence: 99%
“…3 The reliability of this new system was assessed by Lee et al, 5 and found a multitude of possible combinations, a moderate interobserver reliability (0.56), a good intrarater reliability (0.85), and 1ABC (25.4%), 1AC (8.7%), and 1ABCD (6.9%) as the more prevalent subclassifications. Later, Li et al 6 tested the accuracy of surgeons with different experience levels in determining the correct classification and found a 71% to 81.7% rate.…”
Section: Introductionmentioning
confidence: 99%